Issues of ubiquitous music archaeology: Shared knowledge, simulation, terseness, and ambiguity in early computer music - Lazzarini, Victor; Keller , Damián; Radivojević , Nemanja (Frontiers in Signal Processing, 2023)
The reconstruction of tools and artworks belonging to the origins of music computing unveils the dynamics of distributed knowledge underlying some of the major breakthroughs that took place during the analogue-digital transition of the 1950s and 1960s. We document the implementation of two musical replicas, the Computer Suite for Little Boy and For Ann (Rising). Our archaeological ubiquitous-music methods yield fresh insights on both convergences and contradictions implicit in the creation of cutting-edge technologies, pointing to design qualities such as terseness and ambiguity. Through new renditions of historically significant artefacts, enabled by the recovery of artistic first-hand sources and of one of the early computer music environments, MUSIC V, we explore the emergence of exploratory simulations of new musical worlds.